Spinal anaesthesia in children under sedation (Mediscope, 2017)
Spinal anaesthesia in children evolved more than hundred years ago and gaining considerable popularity worldwide. In our setups in Bangladesh, this technique has not gained popularity yet but over the past few years this technique has been practiced in some centers. The objective of the present study was to observe the efficacy and safety of spinal anaesthesia under sedation in children scheduled for infra-umbilical surgical procedures. In this study, 67 children of age ranging from 2 to 10 years of either sex, with American Society of Anaesthesioloists physical status I and II, undergoing infra-umbilical surgeries were included. Spinal anaesthesia was administered with Quincke 27 gauge needles between L4L5 or L5-S1 interspace in the lateral position under sedation with ketamine and midazolam. Heart rate, mean arterial blood pressure and oxygen saturation (SpO2) were monitored throughout perioperative period. Complications of sedation and spinal anaesthesia were recorded and managed accordingly. Among 67 children, male and female were 62 (92.5%) and 5(7.5%), respectively. The mean (SD) age, body weight, American Society of Anaesthesiologists physical status I and II was 5.2 (2.1) years, 15.5 (4.8) kg, 60 (89.6%) and 7 (10.5%), respectively. Successful spinal anaesthesia was done in all cases. The incidences of side effects of sedation were transient apnoea 1 (1.5%), desaturation (SpO2